Characterization of Fusarium graminearum and Fusarium vorosii originated from Small Cereals Grain in Serbia - Obradović, Ana; Stepanović, Jelena; Bulajić, Aleksandra; Hrustić, Jovana; Stanković, Goran; Krnjaja, Vesna; Stanković, Slavica (Scientia agricola, 2025)
ABSTRACT In the present study, the species diversity of Fusarium graminearum species complex was investigated based on morphological, pathogenic, toxicological and genetic characteristics. Fifty-two isolates, derived from small grains from 20 different locations in Serbia, were studied. The phylogenetic analysis of seven selected sequences of three gene regions, translation elongation factor 1-alpha (TEF-1α), histone H3, and β-tubulin, revealed that six isolates were identified as F. graminearum sensu stricto and one as Fusarium vorosii. The TEF-1α and histone H3 genes were found to be sufficiently informative to distinguish the species F. vorosii. These species are of particular concern due to their ability to synthesize mycotoxins that affect both human and animal health. In this study, it was confirmed that all isolates tested belong to the 15ADON chemotype. Since previous investigations have shown that climate change is the leading cause of the appearance of new, potentially more toxic species, future research must pay special attention to changes in the population of this complex. Given that there is little information in the literature about the damage of the F. vorosii species in the production of small grains, this work aimed to examine its aggressiveness and toxicity and thus determine the potential danger of its spreading. Results of the present study showed that the genetic diversity of isolates of F. graminearum species complex (FGSC) in Serbia, as well as their potential for toxin production and aggressiveness, indicate that continuous study of this species is necessary, both in Serbia and the world outside.